Relationship between Behavior, Occupation and Abuse of Psychotropic Drugs and Addictive Substances with Cases of Sexual Violence by Partners Against Women Recorded at the Women Crisis Center in Padang City - Muhammad Zaldy Rasyid Putra; Aladin Aladin; Firdawati Firdawati (Universitas Andalas, 2023)
Background : One of the main issues affecting reproductive health is sexual violence. Sexualviolence is the third most common form of violence against women (30%) of all cases. Basedon data from the Woman Crisis Center (WCC) in Padang, cases of sexual violence havecontinued to increase. There are four main determinants of sexual violence including thesocial environment, community, individual and relationship.Methods: A case-control study is designed to help determine if an determinants is associatedwith an outcome. This study was conducted on 66 samples, 33 of whom were female victimsof sexual violence by partners registered at the WCC. The B-SAFER questionnaire is used asan instrument to assess descriptions of sexual violence committed and psychosocialassessment of the factors underlying the occurrence of sexual violence. Chi-Square test andlogistic regression are used to analyze the relationship between variables.Results: There is no significant relationship between the abuse of psychotropic drugs and theincidence of sexual violence. However, there is a significant relationship between a history ofnegative behavior (p = 0.0001) and disruption of job stability (p = 0.0002) to incidents ofsexual violence. Between this two, negative behavior is the factor that most contributes to theincidence of sexual violence against women, but it is not statistically significant.Conclusion: Behavior is the most important factor in the occurrence of sexual violence, butstatistically it is not significant. There is no variable that determines sexual violence becausethe concept of sexual violence is a complex and polymorphic phenomenon. Further studiesare needed in determining the role of other factors that play a role.